2014
DOI: 10.1007/s00276-014-1343-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of phrenic nerve course in relation to neck dissection

Abstract: The present study sought to clarify the course of the phrenic nerve and its correlation with anatomical landmarks in the neck region. We examined 17 cadavers (30 sides). In each, the phrenic nerves was dissected from the lateral side of the neck, and its position within the triangle formed by the mastoid process and sternal and acromial ends of the clavicle was determined. The point where the phrenic nerve arises in the posterior triangle was found to be similar to the point where the cutaneous blanches of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On occasion (incidence not reported) the phrenic nerve was found within the triangles reported by Singal et al [27]. The course of the phrenic nerve in the neck has been described as originating from the cervical plexus in the posterior triangle of the neck, descends and runs obliquely across the anterior scalene muscle and finally, runs anterior to the subclavian artery before entering the thorax [14,20]. However, other studies suggest that the phrenic nerve descends vertically across the anterior scalene muscle [4,10,13,29].…”
Section: Discussionmentioning
confidence: 78%
“…On occasion (incidence not reported) the phrenic nerve was found within the triangles reported by Singal et al [27]. The course of the phrenic nerve in the neck has been described as originating from the cervical plexus in the posterior triangle of the neck, descends and runs obliquely across the anterior scalene muscle and finally, runs anterior to the subclavian artery before entering the thorax [14,20]. However, other studies suggest that the phrenic nerve descends vertically across the anterior scalene muscle [4,10,13,29].…”
Section: Discussionmentioning
confidence: 78%
“…The aberrant origin of the TCT can lead to potential impairment of the PN. Hamada et al [5] also reported that lateral displacement of the PN could increase the risk of PN injury during internal jugular or subclavian venous catheter placement and brachial plexus block. In addition, marked lateral deviation and subsequent strain of the PN in the neck could increase the risk of nerve injury or nerve dysfunction [16].…”
Section: Discussionmentioning
confidence: 99%
“…The phrenic nerve arises from C3–5 before providing motor innervation to the diaphragm [ 12 ], and despite demonstrating a C2 sensory blockade our patient retained at least partial diaphragmatic function exhibited by the ability to initiate breaths. Differential nerve block in which sensory blockade is several levels higher than motor blockade may occur with both spinal and epidural anesthesia [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%